ACTIVITY OPTIMIZATION AND IMPLICATION TO RESOURCE MANAGEMENT AND RURAL DEVELOPMENT IN THE KAINJI LAKE FISHING COMMUNITIES, NIGERIA - TAFIDA, A. A; ADEBAYO, A. A.; GALTIMA, M.; MODU, B.; RAJI, A. (Nigerian Journal of Fisheries, 2011)
The complexities in resources management of Kainji Lake, which reflect on the economy, environment, cultural and social life of the people remain a central concern to many authorities, organizations, institutions, agencies and NGOs, lead to the development of several approaches to address the problem. In this paper, a more convincing approach using empirical evidences from the field is reported. A model was developed and used to practically test data on livelihood activities collected from 30 fishing communities in Kainji Lake basin selected using stratification technique. The result revealed that rearing of free range chicken and livestock are the optimum and best rewarding activities of the available resources in the rural communities. It is hoped that the result will deter the fishers from intensifying fishing efforts and elicit them to the realization and engagement in most rewarding activities hence sustaining the fisheries resources for future generation and improving the fisher’s wellbeing.